The Government Policy of Jepara Regency in Traditional Market and Modern Store Arrangements - Muhammad Zainudin (International Journal of Small and Medium Enterprises and Business Sustainability, 2020)
Modern stores have experienced very rapid development, this needs to be done supervision, regulation, and guidance on the development of modern stores and traditional markets in the hope that it can run in harmony, so as to protect the traditional market from the rush of modern stores Jepara Regency Government issued a policy with Regional Regulation No. 3 Year 2010 concerning the Arrangement of Traditional Markets, Shopping Centers, and Modern Stores, which currently has undergone changes namely Regional Regulation Number 14 of 2017 Concerning the Management of People's Markets and Supermarkets. The discussion in this study covers the Regional Government Policy of Jepara Regency in structuring traditional markets and modern stores, besides that, this study also analyzes the implementation of the policies issued by the Government of Jepara Regency. The method of approach used is sociological juridical, with the specification of the research used is analytical descriptive of the policies of the Regional Government of Jepara Regency and the implementation of the policy based on the Regional Regulation of the District of Jepara Number 14 Year 2017 Concerning the Arrangement of People's Markets and Supermarkets